Pengaruh Model Pembelajaran Kooperatif tipe Team Assisted Individualization Terhadap Pemahaman Konsep Matematis Peserta Didik Kelas VIII SMP Pembangunan Laboratorium UNP Padang - GEBI ANNISA (Jurnal Edukasi dan Penelitian Matematika, 2019)
Abilityyof mathematicall understanding concepts isi one of mathematics learning purpose. Observations which hadi been done iniclass VII SMP Pembangunan Laboratorium UNP showed that mathematics llearning process was not able to improved students'imathematical understanding concepts optimally. This was cause by thelearningi modelthat had not able to improved students', mathematical understandingiconcepts. Oneeefforttthat could beedone was to applyy the Generative Learning iModel. This typeeoffresearch was quasieexperimentalwwith researchi designnwas StaticGGroupdDesign. Based0on the hypothesis test results could be concluded that ability of students’s mathematical understanding concepts who learned by used generative learning model was better than students‘s’ability of mathematical understanding concepts who learned by used conventionall learning in class VII SMP Pembangunan Laboratorium. Keywords ―  Ability of00Mathematical Understanding Concepts, Mathematics Learning, Generative Learning Model